Institutional conditions for preparing critically reflective TEFL teachers in the PGDT Program of three Ethiopian universities - Roba Danbi; Dereje Tadesse (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2019)
This paper assesses the role played by the institutional context in the preparation of critically reflective TEFL teachers in the Postgraduate Diploma in Teaching (PGDT) program of Dilla, Haramaya, and Hawasa Universities, Ethiopia. It examines the extent to which structured opportunities for reflection are used in the three institutions. A combination of quantitative and qualitative research methodologies was employed for collecting information regarding reflective practice in the PGDT program of the three universities. Multilevel mixed-method sampling techniques were utilized to select participants. Data were collected using questionnaires, semi-structured interviews and observation, and interpreted using simple statistical analysis and descriptive narrative approach. The study shows that most of the participants lack sufficient theoretical and practical knowledge of reflective practice. It shows that structured opportunities for reflection were not created for student teachers to practice reflection. The researchers, therefore, recommend that the government, curriculum designers, teacher education institution, and teacher educators create a common understanding about the goal of the program, and deliberately setup some structured opportunities to promote reflection in the institutions.